Fundamental functions of peripheral and core pyridine rings in a series of bis-terpyridine derivatives for high-performance organic light-emitting devices. Issue 38 (14th September 2016) - Watanabe, Yuichiro; Yoshioka, Ryo; Sasabe, Hisahiro; Kamata, Takahiro; Katagiri, Hiroshi; Yokoyama, Daisuke; Kido, Junji
Abstract : In this study, we comprehensively investigated a series of bis-terpyridine isomers, n -TerPyB, as optoelectronic materials. Abstract : In this study, we comprehensively investigated a series of bis-terpyridine isomers, n -TerPyB, as optoelectronic materials. As a result, we have revealed the fundamental roles of the peripheral and core pyridine rings of TerPyB. The peripheral four pyridines deepen the ionization potential because of their electron-withdrawing properties, and form intramolecular hydrogen bonds (H-bonds) for 2-TerPyB and intermolecular H-bonds for 3-TerPyB and 4-TerPyB. Intermolecular H-bonds in the solid state were observed to play critical roles in determining the molecular aggregation behavior and in enhancing the horizontal molecular orientation and electron mobility. Furthermore, we have revealed that the two fundamental roles of the core pyridines are (i) to render the molecular structure planar via intramolecular H-bonds and (ii) to increase the E a to enhance electron injection without sacrificing electron mobility. Finally, we successfully fabricated proof-of-concept organic light-emitting devices (OLEDs) using TerPyB as an electron-transporter. An OLED with 3-TerPyB exhibited an extremely low operating voltage of 2.2 V at a luminance of 1 cd m −2 ; the power efficiency and the external quantum efficiency of the device were 104 lm W −1, and 23.5% at 100 cd m −2, respectively. We believe that these results open new possibilities in terpyridine chemistry and materials science.